Perceptions of Students of the Islamic Religion Education Study Program on Lecturer Professionalism at the Faculty of Tarbiyah and Teacher Training Raden Fatah State Islamic University Palembang - Alihan Satra; Herwan Efendi; Ade Akhmad Saputra; Ibnu Rozali; Lia Efriliyanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
This research aims to determine the Perceptions of Students of the Islamic Religion Education Study Program on the Professionalism of Lecturers at the Faculty of Tarbiyah and Teaching Sciences, State Islamic University of Raden Fatah Palembang. In this research using qualitative methods, qualitative research. The results of the research show that the perceptions of students of the Islamic Religious Education Study Program towards Lecturer Professionalism at the Tarbiyah and Teacher Training Faculty of UIN Raden Fatah Palembang, reveal varying perceptions, between one student and another, because everyone who expresses perceptions critically is influenced by feelings, experiences, thinking abilities, and other aspects according to what is felt, then their perception can be revealed. On average according to students regarding the professionalism of lecturers in terms of lecturer pedagogic competence, of course there is no doubt from the scientific field, insight, educational foundation, but all of that cannot be denied that there are also some lecturers who do not apply their pedagogic competence as there are some lecturers who do not use media and methods varied learning so that lectures feel bored and monotonous.